"Isolated" Suprascapular Neuropathy: Compression, Traction, or Inflammation?. Issue 2 (26th February 2018) - Le Hanneur, Malo; Maldonado, Andres A; Howe, Benjamin M; Mauermann, Michelle L; Spinner, Robert J
Abstract: BACKGROUND: Several hypotheses have been proposed for the pathophysiology of suprascapular nerve (SSN) palsy, including compression, traction, and nerve inflammation. OBJECTIVE: To provide insight into the pathophysiology of isolated nontraumatic SSN palsy by performing critical reinterpretations of electrodiagnostic (EDX) studies and magnetic resonance (MR) images of patients with such diagnosis. METHODS: We retrospectively reviewed all patients referred to our institution for the past 20 yr with a diagnosis of nontraumatic isolated suprascapular neuropathy who had an upper extremity EDX study and a shoulder or brachial plexus MR scan. Patient charts were reviewed to analyze their initial clinical examination, and their original EDX study and MR images were reinterpreted by an experienced neurologist and a musculoskeletal radiologist, respectively, both blinded from the authors' hypothesis and from each other's findings. RESULTS: Fifty-nine patients were included. Fifty of them (85%) presented with at least 1 finding that was inconsistent with an isolated SSN palsy. Forty patients (68%) had signs on physical examination beyond the SSN distribution. Thirty-one patients (53%) had abnormalities on their EDX studies not related to the SSN. Twenty-two patients (37%) had denervation atrophy in other muscles than the spinati, or neural hyperintensity in other nerves than the SSN on their MR scans, without any evidence of SSN extrinsic compression. CONCLUSION: The great majority of patients with presumed isolated SSN palsy had clinical, electrophysiological, and/or imaging evidence of a more diffuse pattern of neuromuscular involvement. These data strongly support an inflammatory pathophysiology in many cases of "isolated" SSN palsy.